The Influence of Biological Asset Intensity, Profitability, and Firm Size on Biological Asset Disclosure in Agricultural Companies - Trifosa, Felicia; Sjarief, Julianti (SIMAK, 2025)
This study aims to analyze the effect of biological asset intensity, profitability, and company size on biological asset disclosure. The population used in this study were agricultural companies listed on the Indonesia Stock Exchange (IDX) in 2020-2022 amounting to 73 companies. The sample of this study was obtained by purposive sampling method with a total of 72 data. The data used is secondary data obtained from the company's audited annual report obtained from the Indonesia Stock Exchange (IDX) website, namely www.idx.co.id. The method for conducting the analysis used is descriptive statistics and multiple linear regression analysis. Data processing is done with IBM SPSS Statistics software version 25. The results of this study indicate that profitability negatively affects the disclosure of biological assets. Meanwhile, biological asset intensity and company size have no effect on biological asset disclosure.